Value propositions in heritage tourism site business models in the context of open innovation knowledge transfer - Adam R. Szromek (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This article discusses the structures of value propositions in cultural heritage tourism site business models in the context of the concept of open innovation. The objective of the study is to identify value propositions in tourism sites and the tendency of managers to use open innovation. The analysis was based on the example of European cultural heritage tourism sites associated with the European Route of Industrial Heritage. The research process included literature analysis and empirical research in the form of interviews conducted with managers of 73 sites. The research allowed for identifying 16 key values observed in the business models of cultural heritage tourism sites and then classify them into three groups, i.e., values proposed to the customer, values captured by the enterprise and social values. The following values were of the highest importance: promotion of historical industrial heritage, satisfying cognitive needs, acting as a symbol of the area, brand strengthening and organization of tourist traffic, so that the industrial heritage is preserved. It was noticed that some values were significantly correlated with the attitudes of managers towards the exchange of knowledge within open innovation. The majority of managers participating in the research were convinced that the revitalization of cultural heritage sites and the business models of these sites should be in the form of open innovation. The limitation of the research carried out is the inability to deepen the interviews, which was caused by the lack of direct contact with managers due to the COVID-19 pandemic.
Keywords: 650; business model; Europe; heritage tourism; open innovation; value proposition